Models and statistical properties of the results of angular measurements - Бабак, В.П.; Куц, Ю.В.; Щербак, Л.М. (Proceedings of National Aviation University (archive), 2006)
The models of a casual corner on a plane and its probability characteristics are considered. Comparative analysis of the casual data and casual corner characteristics at statistical measurements is executed. The received results are applied for the decision of statistical phase shifts measurements tasks.